PENGEMBANGAN KOMIK DIGITAL BERBANTUAN CANVA PADA PEMBELAJARAN BAHASA INDONESIA MATERI BERTUKAR ATAU MEMBAYAR UNTUK SISWA KELAS IV SD - Syahputri, Widia; Putri Juwita; Sutarini; Umar Darwis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The process of learning Indonesian in grade IV on the exchange or payment material still faces several challenges that hinder the effectiveness of learning. Low student grades are caused by the lack of active participation in learning, which is exacerbated by the use of conventional methods that tend to be boring. The lack of diversity of learning resources and the use of technology in learning also makes the material less interesting and difficult for students to understand. To improve the quality of learning, it is necessary to make changes to the teaching method and the use of more innovative and technology-based learning media such as the development of digital comic media assisted by Canva. This research method is development (Research and Development) with a 4D model which is an extension of Define, Design, Development and Dissemination. The instruments used in this study were questionnaires, test questions and documentation. The validity of digital comic media from input from material experts, namely lecturers, got a score of 96% out of 10 statements. The validity of digital comic media from input from media experts, namely lecturers, got a score of 96% out of 9 statements. The practicality of digital comic media based on teacher responses got a score of 96% out of 10 statements. The effectiveness of comic media based on student responses scored 80% out of 15 questions consisting of 9 students. From the validation data, practicality and effectiveness, the development of digital comic media assisted by Canva in learning Indonesian language material on exchanging or paying for grade IV elementary school students is declared Valid to be used as teaching materials in the learning process.